Pendampingan Belajar Siswa Melalui Kegiatan Ekstrakurikuler Rohis di Bidang Ceramah Agama di SMKN 3 Palangka Raya - Nur Indah Sari; Muhammad Redha Anshari; Ana Kameloh Dian (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Extracurricular activities of Rohani Islam (Rohis) have an important role in character building and developing students' religious skills. This article aims to describe the process of mentoring student learning through Rohis extracurricular activities, especially in the field of religious lectures at SMKN 3 Palangka Raya. The method used in this activity is structured mentoring with a participatory approach. The results of this mentoring showed an increase in students' confidence in delivering religious lectures as well as their understanding of Islamic materials. This activity also has a positive impact in strengthening morals and religious values among students.